2019
DOI: 10.1109/access.2019.2910833
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Exclusive Lanes for Connected and Autonomous Vehicles on Freeway Traffic Flow

Abstract: The intelligence of connected and autonomous vehicle (CAV) is insufficient to deal with the complex road conditions. However, the application of exclusive lanes bypasses the long wait for the technology to mature. Prior to the maturity of intelligent transport systems (ITSs), it's a feasible solution in terms of technology and cost to set up exclusive lanes. In this way, CAVs will form an efficient and energy-saving autonomous fleet. An improved cellular automata model is used to study the effect of setting up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(29 citation statements)
references
References 34 publications
1
28
0
Order By: Relevance
“…ere are two major approaches for exclusive lane research studies: analytical modeling and computer simulation. One of the springboards is from the improvement of traffic flow, including increasing string stability, capacity, or preventing CAVs degraded to AVs (without cooperative) [23][24][25][26]. e above studies revealed the pros and cons of setting up exclusive lanes from the traffic flow theory perspective.…”
Section: Literature Reviewmentioning
confidence: 99%
“…ere are two major approaches for exclusive lane research studies: analytical modeling and computer simulation. One of the springboards is from the improvement of traffic flow, including increasing string stability, capacity, or preventing CAVs degraded to AVs (without cooperative) [23][24][25][26]. e above studies revealed the pros and cons of setting up exclusive lanes from the traffic flow theory perspective.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Learning from the previous successful experience, the CAV-exclusive lane is a feasible approach to reduce the interaction between CAVs and MVs and to improve the performance of mixed traffic [27][28][29]. Ma and Wang [30] developed a four-lane heterogeneous CA flow model and studied the impact of exclusive lanes for CAVs on the overall flow throughput. His study revealed that the traffic volume of roads with the exclusive lane for CAVs, in most cases, exceeds the operation result of roads without exclusive lanes.…”
Section: Literature Reviewmentioning
confidence: 99%
“…e CA model is one of the most widely applied microscopic simulation models [31]. Although the accuracy is a bit lower compared with other continuous models, advantages such as simplicity of modeling process, good capability of describing driving behaviors, and real traffic characteristics have been demonstrated in the past researches [30]. Some typical CA models including the KKW model [32], MCD model [33], and TS model [34] have been proposed.…”
Section: Modelingmentioning
confidence: 99%
“…A major approach on the study of traffic flow is that based on cellular automata. These models are widely used due to its flexibility to incorporate new rules, high generalizations and rich phenomena capturing features [28,[35][36][37][38][39]. The cellular automata introduced by Nagel and Schreckenberg in [40], also known as the NaSch model, has been widely used to study different mechanism in traffic flow [37,[41][42][43][44][45][46].…”
Section: Cellular Automata and Traffic Flowmentioning
confidence: 99%